Monstress. Volume four, The chosen - Liu, Marjorie M (Image Comics, 2019)
Maika and Corvin make their way through a warped and lethal land in search of Kippa, who is faced with her own terrible monsters. But when Maika comes face-to-face with a stranger from her deep past, startling truths are uncovered, and at the center of it all lurks a dangerous conspiracy that threatens the Known World. Maika is finally close to getting all the answers she ever wanted, but at what price? With war on the horizon-a war no one wants to stop-whose side will Maika choose?